Screen Wall Fire Resistance Investigation - Eremina, Tatiana; Korolchenko, Dmitry; Fadeev, V. E. (Frontiers in Built Environment, 2021)
The assessment of fire resistance for building constructions has been carried out by the solution of the heat engineering problem for heating up building structures under the conditions of non-stationary heat exposure with standard fire conditions. The finite element method (FEM) is used as the solution method. Numerical simulation of heating of considered building structures under fire conditions was carried out using the Ansys Mechanical computer complex, which allows for a thermal engineering design to be calculated on the basis of its software model. The resulting functional dependence allows for determining the actual fire resistance of Pf depending on the thickness of sheets δ of the outer skin made of the basalt fire-proof material, as well as the geometric parameters of the protective screen (δ) depending on the required fire resistance from the condition of compliance with the requirements of constructive fire safety (Pf > Preq). Experimental studies to determine the fire resistance for membrane wall structures showed that an increase in temperature on its unheated surface versus structure temperature prior to testing more than 180 ° С (195 ° С) occurs not earlier than 31 minutes. Upon reaching the critical temperatures on the unheated surface of the membrane wall structure independing on its thickness, the fire resistance limits REI 30-REI 120 are reached.